2001
DOI: 10.1161/hc3501.095287
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Platelet Activation in Homozygous Homocystinuria

Abstract: Background-Severe hyperhomocysteinemia due to cystathionine ␤-synthase deficiency (C␤SD) is associated with early atherothrombotic vascular disease. Homocysteine may exert its effects by promoting oxidative damage. In the present study, we investigated whether in vivo formation of 8-iso-prostaglandin (PG) F 2␣ , a platelet-active product of arachidonic acid peroxidation, is enhanced in C␤SD and whether it correlates with in vivo platelet activation, as reflected by thromboxane (TX) metabolite excretion. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
1
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(67 citation statements)
references
References 29 publications
5
58
1
3
Order By: Relevance
“…In HHcy patients, increased platelet activation has been associated with elevated production of tromboxane A 2 (28)(29)(30). In line with these findings, in MTHFR++ carriers, we found that urine thromboxane metabolites were significantly higher than in healthy individuals.…”
Section: Discussionsupporting
confidence: 88%
“…In HHcy patients, increased platelet activation has been associated with elevated production of tromboxane A 2 (28)(29)(30). In line with these findings, in MTHFR++ carriers, we found that urine thromboxane metabolites were significantly higher than in healthy individuals.…”
Section: Discussionsupporting
confidence: 88%
“…The results of this intervention study are consistent with COX-1 being the main COX isoform involved in TXA 2 biosynthesis in this setting and make it unlikely that the reduction in 11-dehydro-TXB 2 excretion associated with successful H pylori eradication is a reflection of reduced COX-2 expression in the gastric mucosa. 16 The findings in H pylori-positive patients extend similar observations made in other clinical settings such as hypercholesterolemia, 42 diabetes mellitus, 43 cigarette smoking, 48,49 homozygous homocystinuria, 50 visceral obesity, 44 and renovascular hypertension. 51 Thus, regardless of the mechanism(s) responsible for enhanced lipid peroxidation, there is quite convincing evidence from studies in such diverse conditions that enhanced generation of bioactive isoeicosanoids may transduce the oxidant signal associated with a variety of cardiovascular risk factors into a functional platelet response, possibly contributing to enhanced thrombotic risk.…”
Section: Discussionsupporting
confidence: 83%
“…CS-induced platelet activation is mainly attributed to its oxidant content and its ability to generate ROS, specifically superoxide anion 32) ; therefore, vitamin C by neutralizing systemic ROS may inhibit CS-induced platelet activation and can contribute to its anti-atherosclerotic property. Consistent with this hypothesis, our results showed that vitamin C, in a dose-dependent manner, prevented CSEinduced platelet activation and thereby provided protection against the development of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%